Mapeamento dos genes Co-10 e Phg-ON de resistência à antracnose e à mancha angular na cultivar de feijoeiro comum Ouro Negro - Cruz, Anelise da Silva (2012)
Ouro Negro is a highly productive Mesoamerican black-seeded bean cultivar that possesses the major dominant genes Co-10 and Phg-ON, which confer resistance to the pathogens C. lindemuthianum (Sacc.) Scrib and P. griseola (Sacc.) Crous & Braun, respectively. In this study, were elucidate the inheritance of resistance to these two pathogens in Ouro Negro using F2 populations from an Ouro Negro (resistant parent) × Rudá (susceptible parent) cross. Co-segregation analysis revealed that a single dominant gene in Ouro Negro confers resistance to race 73 of C. lindemuthianum and race 63-39 of P. griseola. The resistance genes Co-10 and Phg-ON co-segregated at a distance of 0.9 cM from each other on linkage group (LG) Pv04. Molecular marker g2303350, previously mapped to LG Pv04, segregated with Co-10 and Phg-ON at 0.9 cM and 1.8 cM, respectively. SF101072 also co-segregated with Co-10 and Phg-ON at 7.8 and 8.7 cM, respectively. Allele segregation analysis in the BAT93/Jalo EEP558 recombinant population revealed that g2303350 and SF101072 segregated in the expected 1:1 ratio. Due to their physical linkage in a cis configuration, Co-10 and Phg- ON are inherited together and can be monitored indirectly with the markers g2303350 and SF101072. The authors propose that Ouro Negro?s genes for resistance to anthracnose and angular leaf spot should be named as locus Co-10/Phg-ON. These results provide data relevant for common bean breeding programs using markerassisted selection and can reduce the time and costs associated with the pyramiding of these two disease resistance genes in commercial cultivars.